The Impact of E-Filing and Digital Tax Administration on Taxpayer Compliance in Emerging Economies: Evidence from Lombok - Restu Bagus P; Sulkiah Sulkiah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Digital transformation has become a fundamental pillar of tax administration reform in many developing economies. This study investigates the impact of e-filing and digital tax administration on taxpayer compliance, with digital literacy as a moderating variable, using evidence from Lombok, Indonesia. A quantitative explanatory approach was employed using survey data from 92 taxpayers who had used e-filing for at least two consecutive years. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that e-filing has a significant positive effect on formal tax compliance (β = 0.32; p < 0.01), while digital tax administration significantly influences material compliance (β = 0.28; p < 0.01). Furthermore, digital literacy significantly moderates the relationship between digital tax administration and taxpayer compliance (β = 0.21; p < 0.05), indicating that taxpayers with higher digital literacy benefit more from digitalization. The model explains 56% of the variance in taxpayer compliance (R² = 0.56) with strong predictive relevance (Q² = 0.41). This study confirms that digital tax systems can effectively enhance compliance, provided that digital infrastructure and taxpayer literacy are adequately developed. The findings strengthen the applicability of the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) in digital taxation contexts. Practically, this study offers policy implications for the Indonesian Directorate General of Taxes (DJP) to enhance digital literacy education and optimize digital tax systems, especially in underdeveloped regions such as East Lombok.